Protective Effect of Nanoparticles Loaded with Black Rice Anthocyanins on Caco-2 Cell Damage - LIU Yaqi, ZHOU Na, FENG Mengmeng, AI Xin, ZHAO Lei, ZHAO Liang (Shipin Kexue)
In this study, bovine serum albumin (BSA) and genipin (GP) were used to prepare BSA nanoparticles loaded with black rice anthocyanins (BRA-BSAGP) to improve the stability and bioactivity of BRA. The interaction between BSAGP and BRA was analyzed, the release characteristics of BRA-BSAGP during simulated gastrointestinal digestion were explored, and the ameliorative effect and mechanism of BRA-BSAGP on Caco-2 cell damage induced by dextran sulfate sodium (DSS) were investigated. BRA-BSAGP showed a uniform spherical morphology with an encapsulation efficiency of (81.10 ± 0.08)%. Fourier transform infrared spectroscopy (FTIR) and X-ray diffraction (XRD) analysis confirmed the successful encapsulation of BRA in BSA nanoparticles. In vitro gastrointestinal digestion demonstrated that BRA-BSAGP nanoparticles effectively delayed the release of BRA, with release percentages of 22.51% and 20.10% under simulated fasting and fed conditions, respectively. BRA-BSAGP significantly increased the survival rate of Caco-2 cells induced by DSS and up-regulated the expression of tight junction proteins (Claudin-1, occludin, and ZO-1). This study provides a theoretical basis for the application of BRA in developing functional foods for alleviating ulcerative colitis.